Dampak Kehadiran Transportasi Online Maxim Car Terhadap Pendapatan Transportasi Umum di Kota Sorong - La Ode Rablan; Karfin; Rabiudin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the impact of Maxim's presence on the income of conventional public transportation drivers in Sorong City. The study used a comparative quantitative approach involving 120 public transportation drivers selected through purposive sampling. Data were collected using a closed-ended questionnaire containing information on income, number of passengers, operating hours, and driver perceptions before and after Maxim's presence. Data analysis was conducted using descriptive statistics, normality tests, and paired sample t-tests. The results showed that Maxim's presence had an impact on the income of conventional public transportation drivers, followed by a decrease in the number of passengers, even though the drivers' operating hours tended to increase. The results of the hypothesis test showed a significant difference in income before and after Maxim's operation (p < 0.05). These findings indicate that app-based transportation has become a form of digital disruption that affects the economic sustainability of conventional public transportation drivers. Therefore, adaptation efforts are needed through improving service quality, structuring the transportation system, ensuring fare certainty, and strengthening digital transformation so that public transportation remains competitive amidst the development of app-based transportation.